Time to consider ovarian tissue cryopreservation for girls with Turner's syndrome: an opinion paper. Issue 3 (20th June 2019) - Jeve, Yadava Bapurao; Gelbaya, Tarek; Fatum, Muhammad
Abstract: Turner's syndrome (TS) is the most common sex chromosome abnormality in women. In addition to short stature and gonadal dysgenesis, it is associated with cardiac and renal anomalies. Due to rapid follicular atresia, the majority of women with TS suffer from primary ovarian insufficiency around puberty. Thus far, donor oocyte conception has been the key fertility option for these women. With advancing technology, ovarian tissue cryopreservation (OTCP) has emerged as a clinically justifiable option especially for pre-pubertal girls with cancer. Recently published results following the use of cryopreserved ovarian tissue are reassuring. It would be prudent to consider the extension of these technological and scientific advances to other conditions, such as TS, where accelerated follicular atresia is suspected. It is possible to obtain competent oocytes from cryopreserved ovaries of girls with TS provided the ovaries were preserved before ovarian failure. However, it is a complex decision whether and when to offer OTCP as a fertility preservation (FP) option for girls with TS. The rate of decline in fertility is variable in girls with TS and can be more complex in cases with mosaicism. On the other hand, OTCP has shown some promising results in patients with cancer, which can potentially be replicated in TS and other benign indications of patients at risk of premature ovarian failure. There are proven psychological and clinical benefits of FP. Thus, an argument could be made for offering OTCP to these patients to endow these girls with the option of having biological fertility using this innovative technology. Ethical, clinical and psychological dilemmas should be considered, discussed and addressed before considering such a novel approach. We believe that the time has come to start this discussion and open this avenue of FP for girls with TS.